KOMUNIKASI PEMASARAN DALAM MENINGKATKAN LOYALITAS PELANGGAN (Study Kasus Di Progresif Digital Printing And Advertising Cabang Simo, Boyolali Dalam Tiga - Bedjo Soekarno & Maya Sekar W, Ahmad Robianto (Transformasi, 2015)
This study aims to determine the marketing communications conducted by progressive digitalprinting and advertising branch simo in increasing customer loyalty. In this study, using thetheory of Kotler's marketing communications and customer loyalty theory of Buchari Alma. Themethod used in this research is descriptive qualitative. The technique of collecting data usinginterviews, observation and documentation so that the data are presented accurately. Data wereanalyzed using an interactive analysis and research models move between the three componentsof data: data reduction, data presentation, and concluding with the data collection component.The results of analysis of this study that conducted marketing communications company managedto increase customer loyalty by using marketing communication in the form of promotion mixwhich includes Advertising (Advertising) were performed using print media such as banners,Sticker affixed in the car or commonly known as (Branding Car) and face to Face (PersonalSelling) conducted by plunging directly into the field came to prospective customers to provideinformation and the Sales Promotion (Sales Promotion), which is done by giving bonuses, freeoffers and discounts.Keywords: Marketing Communications, Customer Loyalty, Progressive